THEORETICAL APPROACHES TO GRADATION IN LINGUISTICS: AN OVERVIEW (Web of Teachers: Inderscience Research, 2025)
This article provides an overview of gradation in linguistics, exploring its manifestations in phonology, morphology, semantics, syntax, and pragmatics. It discusses key theoretical approaches and illustrates how gradation expresses varying degrees of comparison, intensity, and modality. Through examples, it highlights the importance of contextual and social factors in understanding gradation, emphasizing its role in effective communication and linguistic theory.